EVALUATION OF OXIDATIVE STRESS AND ANTIOXIDANT STATUS BETWEEN TYPE II DIABETES PATIENTS AND HEALTHY POPULATIONS - Nelli, Sudharshan Reddy; Sharma, Nilesh Kumar; Kumar P, Manoj; Singh, Surya S (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Introduction: The aim of the present study is to profile the serum antioxidative enzymes, catalase (CAT), glutathione peroxidase (GPx), and superoxide dismutase (SOD) level in Type II diabetes mellitus patients in comparison to healthy volunteers in the South Indian population. Methodology: A prospective, observational, case–control study was conducted for 1 year with a total of 120 patients including 90 Type II diabetes patients (case group) and 30 healthy volunteers (control group). Blood was collected from these volunteers, and serum levels of CAT, GPx, and SOD were estimated. In addition, they were also monitored for the fasting blood glucose, glycated hemoglobin (HbA1c), and postprandial blood glucose. Data were statistically analyzed applying unpaired t-test and Pearson correlation with the statistical significance of p<0.05. Results: The diabetes patient group showed significant higher levels of glycated hemoglobin, fasting blood glucose and postprandial blood glucose (p<0.0001). There was asignificant lower level in the RBC levels of superoxide dismutase in case group compared to control group 3859.00±381.8 (mean+SD) and 5862.7±209.45 (mean+SD) Units per gram Hb, (t-value 27.35, p-Value <0.0001). Catalase and Glutathione peroxidase RBC levels also showed significant lower levels in the case group compared to the control group (catalase 212.7±19.08 (mean±SD) and 396.47±10.83 (mean±SD) Units per gram Hb; T value=50.07 and p<0.0001)(Glutathione peroxidase11.7 ±01.09 (mean +SD) and 18.6 ± 01.00 (mean +SD) Units per gram Hb; t value=30.26 and p<0.0001). Conclusion: A significant reduction in serum levels of antioxidative enzymes, CAT, GPx, and SOD was observed in the South Indian Type II diabetes patient population.